Fast Software Encryption : 22nd International Workshop, FSE 2015, Istanbul, Turkey, March 8-11, 2015, Revised Selected Papers - Leander, Gregor; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 22nd International Workshop on Fast Software Encryption, held in Istanbul, Turkey, March 8-11, 2015. The 28 revised full papers presented were carefully reviewed and selected from 71 initial submissions. The papers are organized in topical sections on block cipher cryptanalysis; understanding attacks; implementation issues; more block cipher cryptanalysis; cryptanalysis of authenticated encryption schemes; proofs; design; lightweight; cryptanalysis of hash functions and stream ciphers; and mass surveillance.
Block cipher cryptanalysis -- Understanding attacks -- Implementation issues -- More block cipher cryptanalysis -- Cryptanalysis of authenticated encryption schemes -- Proofs -- Design -- Lightweight -- Cryptanalysis of hash functions and stream ciphers -- Mass surveillance.
Keywords: Data encryption (Computer science).; Computer security; Information Systems; Coding theory; Cryptology; Systems and Data Security; Management of Computing and Information Systems; Coding and Information Theory